Repositioning Sacred Texts in the Age of Post-Truth: A Hermeneutic Approach to Religious Authority and Truth - Rachmatullah Arken (Jurusan Aqidah dan Filsafat Islam Universitas Negri Sunan Gunung Djati Bandung, 2025)
The phenomenon of post-truth has significantly affected religious life in the digital age, where emotional narratives and personal beliefs often overshadow objective truth. This paper explores how post-truth undermines the authority of sacred texts, shifting religious understanding towards subjective interpretations driven by personal and group affiliations. Using Gadamer's hermeneutics, particularly the concept of “fusion of horizons,” this study offers a critical framework for reinterpreting religious texts in a dynamic and context-sensitive manner. The research employs a qualitative literature review method, analyzing works on hermeneutics, post-truth, and theological interpretation. The findings reveal that personal authority and emotional attachment to religious figures have become dominant in shaping religious understanding, often at the expense of rational and text-based theological discourse. Furthermore, the relativization of truth in post-truth societies challenges the absolute nature of divine revelation, leading to fragmented interpretations of sacred texts. However, rather than viewing post-truth solely as a threat, this paper argues that it presents an opportunity for theological renewal. By integrating critical hermeneutics with a contextual approach, sacred texts can remain relevant as sources of absolute truth while being responsive to contemporary social and moral challenges. Thus, hermeneutics serves as a bridge between the immutable essence of revelation and the evolving human understanding.